Results of phosphene electrostimulation treatment of patients with primary open-angle glaucoma - V. A. Putienko; V.S. Ponomarchuk (Ukrainian Society of Ophthalmologists, 2016)
The purpose was to assess the efficacy of phosphene electrostimulation in patients with stage II and III of primary open-angle glaucoma with compensated IOP. Material and Methods. We followed up 26 patients (31 eyes) with drug-compensated primary open-angle glaucoma (POAG). 16 eyes with stage II glaucoma comprised the first group. The second group consisted of 15 eyes with stage III glaucoma. Treatment included 10 PES standard sessions. Each session lasted 10 minutes. Current dose was selected in every particular case in regard to initial зhosphene threshold of electric sensitivity (PTES) level. Treatment efficacy was assessed according to rate changes in PTES, CFPD in «1.5» and «3» modes and according to changes in computer perimetry data. Results. FES in stage II POAG patients enabled to improve retinal light perception by 19.3% and to increase electrical sensitivity of visual analyzer (phosphene threshold increased by 14.4%). In stage III patients, light perception increased by 14.8%, phosphene threshold of electrical sensitivity increased by 15.2%, and phosphene electrical lability in modes 1.5 and 3.0 increased by 13.5% and 21.1%, respectively, which made it possible to recommend the treatment for this category of patients.